Eesti-Soome uurimisprojekt: võrdlev pilguheit kahe naabermaa 19. sajandi ajaloole - Timo Myllyntaus; Marten Seppel (Eesti Arhivaaride Ühing, 2022)
A research project on Estonia and Finland: Comparative survey on the history of two neighbours in the 19th century (Title in English)